DECISION SUPPORT SYSTEM FOR SELECTING THE BEST EMPLOYEE USING THE COMPLEX PROPORTIONAL ASSESSMENT METHOD AT PT. SEGAR MURNI UTAMA: SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KARYAWAN TERBAIK MENGGUNAKAN METODE COMPLEX PROPORTIONAL ASSESSMENT PADA PT. SEGAR MURNI UTAMA - Robbi, Zidan Nurdin; Utami, Ardhini Warih (Universitas Negeri Surabaya, 2023)
In the era of rapid technological advancement, various applications have been developed to fulfill human needs, providing ease of global information access, and supporting the business world. PT. Segar Murni Utama (MOJOTRAS) endeavors to implement digitalization through a Decision Support System (DSS) based on Complex Proportional Assessment (COPRAS) to select the best employees. This study develops a DSS application that allows Managers, HRD, and Directors to participate in the process. The Spiral model of development is employed in this research, encompassing phases of planning, risk analysis, engineering, and evaluation. The application utilizes Laravel and employs UML in design. It includes features to manage employee data, employee assessment, COPRAS calculations, submission of decision results, and the downloading of decision outcomes. Blackbox Testing is conducted by HRD at PT. Segar Murni Utama to validate the functionality of the application. The research findings indicate that the DSS application using the COPRAS approach can aid in the process of selecting the best employees, enhancing effectiveness and efficiency in the evaluation process within the company. Specific assessments aligned with division criteria and company-wide selections have the potential to reduce bonus expenditures and foster improved employee performance. Thus, this application holds the potential to provide benefits for PT. Segar Murni Utama in decision-making related to the selection of the best employees.